The Effectiveness Of The Bingo Game Method In Mastering Arabic Vocabulary At School: فعالية طريقة اللعبة البنغو على إتقان المفردات العربية في المدرسة - Muhammad Ardy Zaini; Dzurrotun Nafisah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2022)
Based on a note before the research, many students have a lack of dedication to Arabic vocabulary in its semen and memorizing the meaning. You can see it when students are asked about one of the teaching vocabulary, few of them can answer correctly. The objectives in this research are to find out the effectiveness of the Bingo game method on mastering Arabic vocabulary in its pronunciation and memorizing the meaning at Hashem Al-Ash’ari Islamic Intermediate School Lumajang for the school year 2021/2022 AD. In this research, the researcher used the quantitative approach of its experimental type, which is a pre-experimental design in the form of a single group, a tribal and post-test, data collection, unstructured personal interview, multiple-choice test, documentation, and method for selecting a sample with a saturated sample. As for the results of the research, the Bingo game method is effective in improving the mastery of Arabic vocabulary in its pronunciation and memorizing the meaning in the Hashem Al-Ash’ari Islamic intermediate school in Lumajang for the school year 2021/2022 AD as much as the average N-gain (N-gain) Brucene between 56-75 means 67.09, so it entered an effective category Sufficient by reason. So, the research hypotheses in this research are that the hypotheses of Al-Khayari (Ha) are acceptable and the null hypotheses are rejected (H0).